New species of deep-sea demosponges (Porifera) from the Aleutian Islands (Alaska, USA) - Lehnert, Helmut; Stone, Robert; Heimler, Wolfgang (Zootaxa, 2006)
Deep-sea sponge habitat of the Aleutian Islands was investigated with the ROV Jason II. Identification of the more than 60 specimens collected at depths between 179 and 2827 m revealed nine new species of demosponges. Megaciella anisochela sp. nov., Stelodoryx oxeata sp.nov, Monanchora laminachela sp.nov, Echinoclathria vasa sp. nov., Euchelipluma elongata sp. nov., Esperiopsis flagrum sp. nov., Mycale jasoniae sp. nov., Latrunculia velera sp. nov. and Latrunculia occulta sp. nov. are described and compared with congeners of the area.